UPAYA MENINGKATKAN PENGETAHUAN GIZI SEIMBANG MELALUI EDUKASI INTERAKTIF PADA ANAK SEKOLAH DASAR DALAM PROGRAM RAMADHAN KIDS CERIA - Herdiani Siallagan; Eka Puspita Sari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity was carried out with the aim of increasing children's understanding and forming better vegetable and fruit consumption habits from an early age through health education at the Baiturrahim Mosque in Kotaraja. The implementation method of this activity included health education, question and answer sessions, and evaluation through pre-tests and post-tests. The pre-test was conducted before the intervention to determine the participants initial level of knowledge, and the post-test was conducted after the intervention to measure the increase in participants knowledge. The participants of this activity were elementary school-aged children who participated in the Ramadhan Kids Ceria program with a total of 24 participants. Before counseling, most participants (45.8%) had sufficient knowledge and a small portion (16.7%) had insufficient knowledge about balanced nutrition, while only 37.5% had good knowledge. After the intervention, there was an increase in knowledge in participants where the majority of participants (66.7%) had good knowledge, and there was a change in participants who had sufficient knowledge (29.2%) and less (4.1%).